2021
DOI: 10.1182/blood.2019004713
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MALT1 feedback mechanisms enables rational design of potent antilymphoma regimens for ABC-DLBCL

Abstract: MALT1 inhibitors are promising therapeutic agents for B-cell lymphomas that are dependent on constitutive or aberrant signaling pathways. However, a potential limitation for signal transduction–targeted therapies is the occurrence of feedback mechanisms that enable escape from the full impact of such drugs. Here, we used a functional genomics screen in activated B-cell–like (ABC) diffuse large B-cell lymphoma (DLBCL) cells treated with a small molecule irreversible inhibitor of MALT1 to identify genes that mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Moreover, upregulation of BCR pathway components in ABC EVs suggests it to be a potential target for therapy since the loss of B-cell receptor (BCR)-and phosphatidylinositol 3-kinase (PI3K)-activating proteins enhanced sensitivity. By contrast, the loss of negative regulators of these pathways (e.g., TRAF2, TNFAIP3) promoted resistance to MALT1 inhibitors [44]. EVs-containing BCR components are of extreme relevance since immunotherapy options targeting BCR components and auxiliary molecules such as the case of newly CD22 CAR T-cell therapy [45] can function as decoys, leading to disease refractoriness [46].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, upregulation of BCR pathway components in ABC EVs suggests it to be a potential target for therapy since the loss of B-cell receptor (BCR)-and phosphatidylinositol 3-kinase (PI3K)-activating proteins enhanced sensitivity. By contrast, the loss of negative regulators of these pathways (e.g., TRAF2, TNFAIP3) promoted resistance to MALT1 inhibitors [44]. EVs-containing BCR components are of extreme relevance since immunotherapy options targeting BCR components and auxiliary molecules such as the case of newly CD22 CAR T-cell therapy [45] can function as decoys, leading to disease refractoriness [46].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analyses revealed strong expression of TRAF2 in ABC-like DLBCL with significant association with reduced progression-free survival [ 228 ]. Moreover, functional genetic screens in DLBCL cell lines identified TRAF2 as a factor conferring resistance against mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1) inhibitor and the cereblon E3 ligase–modulating agent CC-122 [ 229 , 230 ]. One of the somatic mutations in TRAF2 identified in DLBCL results in enhanced TRAF2-dependent classical NFκB activation [ 226 ].…”
Section: Traf2 and The Nfκb System In Oncogenesismentioning
confidence: 99%
“…Human mucosa-associated lymphoid tissue protein 1 (MALT1) is a protease and scaffold protein involved in NF-κB signal transduction, which is essential for cell proliferation and survival [ 126 ]. Recent studies have found that MALT1 has therapeutic targeting in ABC-type diffuse large B-cell lymphoma (ABC-DLBCL) [ 127 ]. Studies have shown that inhibiting the MALT1 protein causes autoimmune disease and death in mice.…”
Section: Application Of Protac In Anticancermentioning
confidence: 99%